(3HOjY GdeYGfj aj TQM YbjOI GdTjHGfjs - (3YdhGf, Ydj Hf YWjI Hf GdMSf, J (B936 (3g`s ((3eMeO QMeI Gddg Hf GdNWjHs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd eYQaJg QCS eGd GdSYGOI hHYO adeG cGfJ YbjOI GdTjHGfj SdSI GddaX hde GLO dgG TQMG Shi TQM GdfLe Hf bGVj YdLhf SfM aj acQj ZjQ eQI Cf CdMbg HegeGJ hChTMg HJJeGJs
(3BNQgG (B:s
(3PcQ hHg bGd GdMdjej ef GdTGaYjI hGddNej ef GdeGdcjI hGdWMGhj ef GdMfajI hGHf HWI ef GdMfGHdI hbjd ZjQ Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 312s
(3eYLe GdeDdajf (B2 / 476s
(3cTa GdXfhf (B2 / 1142s
(3TPQGJ GdPgH (B8 / 217s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds